Red clover for treatment of hot flashes and menopausal symptoms: A systematic review and meta-analysis. (2nd April 2016) - Ghazanfarpour, M.; Sadeghi, R.; Roudsari, R. Latifnejad; Khorsand, I.; Khadivzadeh, T.; Muoio, B.
Abstract : This study evaluated the efficacy of red clover to relieve hot flashes and menopausal symptoms in peri/postmenopausal women. Electronic databases (MEDLINE, Scopus and the Cochrane Library) were searched. The mean frequency of hot flashes in red clover groups was lower compared with that in the control groups (close to statistical significance). Difference in means (MD) of hot flashes frequency was − 1.99 (− 4.12–0.139; p = 0.067; heterogeneity P > 0.01; I 2 = 94.93%; Random effect model). Subjective (vaginal dryness) and objective (maturation value) symptoms of vaginal atrophy showed a significant improvement with 80-mg dose of red clover. Red clover showed less therapeutic effect on psychology status, sexual problems and sleeping disorders. Red clover consumption may decrease frequency of hot flashes, especially in women with severe hot flashes (≥ 5 per day). Red clover may reduce other menopausal symptoms. Further trials are needed to confirm the current systematic review findings.